Ekstrak Babadotan (Ageratum Conyzoides) Sebagai Agen Antifungi Untuk Mengendalikan Patogen Colletotrichum Sp. Pada Tanaman Terong (Solanum Melongena L.) - Muh Gilang Pratama; Rida Iswati; Wawan Pembengo (Transbahasa, 2025)
This study aims to evaluate the potential of Ageratum conyzoides (babadotan) extract in controlling Colletotrichum sp., the causative agent of anthracnose in eggplant (Solanum melongena L.). The experiment was conducted using a Randomized Block Design (RBD) with six treatments: negative control (F0), positive control inoculated with Colletotrichum sp. without treatment (F1), synthetic fungicide (F2), and babadotan extract at concentrations of 40% (F3), 60% (F4), and 80% (F5), with three replications each. Observed parameters included incubation period, disease incidence, and disease intensity. The results showed that treatments F4 and F5 (60% and 80% concentrations) were the most effective in suppressing the disease. These treatments extended the incubation period to 13.17 and 13.58 days, respectively. Furthermore, the lowest disease incidence was recorded in F4 (1.39% at 58 days after planting and 9.72% at 62 days) and in F5 (0% at 58 days and 2.08% at 62 days). Disease intensity also decreased with increasing extract concentration. These findings suggest that babadotan extract, particularly at 60% and 80% concentrations, has strong potential as a natural alternative to synthetic fungicides in controlling anthracnose disease caused by Colletotrichum sp. in eggplant cultivation.